Measurements at drifting snow at Mizuho Camp, East Antarctica , 1974-1975 - Masayuki Inoue; Kazuo Fujino (National Institute of Polar Research, 1977)
Measurements were carried out simultaneously of drifting snow and wind speed over the surface from 1974 to 1975 at Mizuho Camp using an improved drawer-type drift collector which had a collection efficiency of about 0.55. From the obtained profile of spatial distribution of drift mass flux, it is considered that a layer from the surface to a height of about 25 cm is the one in which the saltation of snow particles prevails and a layer on top of it is the one in which snow particles are suspended by turbulent diffusion. A significant correlation was found between the total drift transport and the wind speed at the height of 10 m above the surface. The total drift transport at Mizuho Camp evaluated from this correlation was about 0.64×10^6 ton・km^・year^.